2020
DOI: 10.1080/24748668.2020.1718458
|View full text |Cite
|
Sign up to set email alerts
|

Conditional analysis of elite beach handball according to specific playing position through assessment with GPS

Abstract: Beach handball needs to continue to develop. For this reason, observational studies that analyze competitive demands are necessary. Therefore, our objective in this work was to carry out performance assessment of the beach handball players regarding specific playing positions during competition, without modifying the specific structure of the game. The study included 57 elite beach handball players. The results showed that significant differences were found in most of the variables studied when the specific pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
68
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(80 citation statements)
references
References 22 publications
9
68
3
Order By: Relevance
“…In the between-genders comparison, higher demands were performed by males in impacts, jumps and player load respect to females, as well as a greater volume of demands. In this sense, the investigations realized by Pueo et al 8 and Zapardiel and Asín-Izquierdo 19 shown similar results in both genders related to the volume of displacements and actions, but higher demands in high-intensity actions in males respect to female beach handball players (high intensity impacts, collisions and high-intensity accelerations and decelerations).…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…In the between-genders comparison, higher demands were performed by males in impacts, jumps and player load respect to females, as well as a greater volume of demands. In this sense, the investigations realized by Pueo et al 8 and Zapardiel and Asín-Izquierdo 19 shown similar results in both genders related to the volume of displacements and actions, but higher demands in high-intensity actions in males respect to female beach handball players (high intensity impacts, collisions and high-intensity accelerations and decelerations).…”
Section: Resultsmentioning
confidence: 57%
“…The monitoring through electronic performance and tracking systems (EPTS) is very extended in handball through optical systems and inertial devices 17,18 . In beach handball, only two previous studies realized by Pueo et al 8 and Zapardiel and Asín-Izquierdo 19 have investigated the workload demands in competition. These studies have shown that players covered a total distance between 600 and 1200 meters, being most of them low-intensity displacements (1-12 km/h), with low-intensity impacts (5-6G) and moderate physiological demands (71-80% HR MAX ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reflecting the studies on indoor handball [6][7][8][9], researches on beach handball focused on physiological and kinematic aspects [10][11][12][13][14], individual and team performance [3,15] and shooting analysis [4,16,17]. Several moderate-to-high intensity activities distributed intermittently throughout the match characterizes beach handball, with males performing more moderate and high intensity accelerations than females [10] and kinematics variables (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…total distance, body load, impacts, speed average) decreasing in the second set for both males and females [13]. In a more recent study [14] differences in the conditional assessment of the specific playing positions (specialist, wing fixed wing, pivot, defender) of elite beach handball players have been studied for male and female players. Significant gender-related differences emerged in the conditional data of competition with differences depending on the playing position, both in men and women.…”
Section: Introductionmentioning
confidence: 99%